(3McheGJ GdLRGFQ hGdeZQH hJhfSs - (3ejShe(B, (3UHjMs ((3YeGf(B:s (3GdefXeI GdYQHjI ddYdhe GdEOGQjI(B,s, 1985)
(3GdEOGQI GdeQcRjI(B- (3hMOGJ GdMce GdeMdj(B( (3GdLeGYGJ GdeMdjI(B)- (3GdhXjaI GdYehejIs
Keywords: (3GdEOGQI(B- (3GdeZQH GdYQHjs